Identifikasi Akuifer Air Tanah menggunakan Metode Geolistrik di Perumahan Gang Jati Baru, Hajimena, Natar, Lampung Selatan - Kumalasari, Isti Nur; RahmiMulyasari, Rahmi; Dewanto, Ordas; Mulyatno, Bagus Sapto; Wibowo, Rahmat Catur; Maulida, Nanda Hanyfa; Hidayatika, Akroma; Hesti, Hesti; Dani, Ilham; Erfani, Sandi (Jurusan Fisika, Universitas Bangka Belitung, 2025)
Groundwater is a basic human need. However, the residents of Perumahan Gang Jati Baru, Hajimena, Natar face significant challenges in meeting their water demands, particularly during the dry season when water availability is critically reduced. To explore groundwater resources in Perumahan Gang Jatibaru, geoelectric measurements need to be conducted. The Schlumberger configuration is used for 1D measurements, while the Wenner-Schlumberger configuration is used for 2D data acquisition. The modeling results indicate the presence of shallow groundwater aquifers at depths ranging from 11.1 to 28.3 meters, and deeper aquifers at depths between 42.7 and 79 meters, characterized by low resistivity values of approximately 13.2 13.2 ohm.m. These findings are corroborated by the 2D resistivity modeling conducted at the study site, which reveals a shallow low-resistivity anomaly (<15.2 13.2 ohm.m) occurring at depths of 10 to 28 meters.